Development of Metal-Free Reductive Processes Using Silanes and Brønsted Acid Activation - Stoneley, Amelia (2024)
Initial discussion centres on the importance of metal-free chemistry and organosilicon chemistry and its application to reductive processes. Silicon’s uses, bonding and activation is also considered in more detail.